(untitled) (Malaysian Journal of Learning and Instruction, 2023)
Purpose - A sublime social attitude (brahmavihāra) has been identified as a crucial aspect of Buddhist Education (BE) for fostering prosocial behavior. Therefore, this study aims to construct and establish the validity of a sublime social attitude scale for prospective teachers of BE, as well as to detect social desirability bias (SDB). Methodology – This is a development research through a survey method using a quantitative approach that produces a scale to measure the brahmavihāra of prospective Buddhist education teachers. The content validity was quantitatively analysed by calculating and comparing three statistical methods for item relevance, namely content validity index, binomial test, and asymmetric score confidence nterval, based on the evaluation of nine experts. Furthermore, empirical testing was conducted using second-order confirmatory factor analysis (CFA) with 233 respondents from a population 1012. The identification of item susceptibility to SDB was carried out through qualitative rating by three raters on a draft of a sublime social attitude scale and empirically confirmed by CFA. Findings - The results showed that brahmavihāra, a psychological attribute consisting of four dimensions, namely loving-kindness, compassion, sympathetic joy, and equanimity, were empirically proven by CFA. Empirical testing resulted in 24 valid items having a fit model with the goodness of fit criteria fulfilled. Further, five items were identified by the experts as potentially vulnerable to SDB, and only one was empirically confirmed to be vulnerable based on the CFA. Significance - The instrument developed in this study could serve as an effective assessment tool for BE instructors and a psychological scale for other stakeholders to measure brahmavihāra in the recruitment of BE teachers.